50 Using A Targeted Teaching Intervention to Drive up the Quality of Discharge Summaries. Shop 75+. (16th March 2021) - Robey, R C; Danson, A; Evans, J; Froggatt, J; Pederson, A; Cross, T; Vilches-Moraga, A; Gaillemin, O
Abstract: Background: Quality improvement project examining discharge communication, and a targeted teaching intervention. Introduction: Poor quality, incomplete or missing discharge summaries (DSs) are associated with avoidable/ameliorable adverse events after discharge [1]; preventable readmission [2, 3]; failure to implement discharge plans [4]; and medication continuity errors [4, 5]. Methods: To review the quality of DSs produced, each month forty representative DSs are randomly selected from four clinical areas and qualitatively assessed (total > 1, 000, August 2017—to date). Alongside this, in August 2018, incoming foundation doctors were surveyed on perceptions of the purpose/importance of DSs, and training provided on writing them. They were resurveyed after teaching delivery in November 2018 and April 2019. Interventions: Data from QI review and survey were used to generate a teaching intervention, in the form of an interactive slide set for delivery in small group settings. This was delivered in weekly mandatory teaching sessions. PDSA cycles were completed for teaching sessions, and the slide set was developed accordingly. Results: After the teaching sessions, we noted improvement in satisfaction with training provided on writing DSs (from 24% to 40%), as well as confidence in writing high-quality DSs (from 28% to 100%). We demonstrated increases in responses including the patient as an intended audience for the DS (from 51% to 84%), and rating "patient information in lay terms" of "high importance" (from 41% to 72%). These changes in perceptions were accompanied by improvement in the quality of DSs produced, particularly with respect to the quality of follow-up actions detailed and the quality of patient information provided in lay terminology. The average monthly proportion of DSs achieving a "great score" in these areas increased from 20% and 28% respectively (August 2017—June 2018), to 44% and 71% (August 2018—March 2019). Conclusions: These data provide proof-of-principle that targeted teaching, constructed around prior questionnaire surveys, improves awareness of the purpose of DCs and leads to improvement in the quality of DSs produced and enhanced patient safety.